Incidence and prognostic impact of post discharge bleeding post acute coronary syndrome within an outpatient setting: a systematic review. Issue 2 (20th February 2019) - Ismail, Nafiu; Jordan, Kelvin P; Rao, Sunil; Kinnaird, Tim; Potts, Jessica; Kadam, Umesh T; Mamas, Mamas A
Abstract : Objective: The primary objective was to determine the incidence of bleeding events post acute coronary syndrome (ACS) following hospital discharge. The secondary objective was to determine the prognostic impact of bleeding on mortality, major adverse cardiovascular events (MACE), myocardial re-infarction and rehospitalisation in the postdischarge setting. Design: A narrative systematic review. Data source: Medline, Embase, Amed and Central (Cochrane) were searched up to August 2018. Study selection: For the primary objective, randomised controlled trials (RCT) and observational studies reporting on the incidence of bleeding post hospital discharge were included. For the secondary objective, RCTs and observational studies that compared patients with bleeding versus those without bleeding post hospital discharge vis-à-vis mortality, MACE, myocardial re-infarction and rehospitalisation were included. Results: 53 studies (36 observational studies and 17 RCTs) with a combined cohort of 714 458 participants for the primary objectives and 187 317 for the secondary objectives were included. Follow-up ranged from 1 month to just over 4 years. The incidence of bleeding within 12 months post hospital discharge ranged from 0.20% to 37.5% in observational studies and between 0.96% and 39.4% in RCTs. The majority of bleeds occurred in the initial 3 months after hospital discharge with bruising the most commonly reported event. Major bleeding increased the risk of mortality by nearly threefold in two studies. One study showed an increased risk of MACE (HR 3.00, 95% CI 2.75 to 3.27; p<0.0001) with bleeding and another study showed a non-significant association with rehospitalisation (HR 1.20, 95% CI 0.95 to 1.52; p=0.13). Conclusion: Bleeding complications following ACS management are common and continue to occur in the long term after hospital discharge. These bleeding complications may increase the risk of mortality and MACE, but greater evidence is needed to assess their long-term effects. PROSPERO registration number: CRD42017062378.